Conducting Assessments of Community-Based Programs for Individuals With Dementia and Their Family Caregivers. - Heid, Allison R; Zarit, Steven H (Gerontologist, 2025)
Although the gold standard for intervention science is the randomized controlled trial (RCT), there is growing emphasis on the practical implementation and evaluation of evidence-based programs in community agencies. Assessment of program efficacy by community-based organizations can confirm planned delivery of services, implementation fidelity, and demonstrate positive outcomes, which can provide justification for funding. Methods and measures used in an RCT, however, often cannot be implemented in nonresearch settings, and different approaches are needed. This manuscript reviews the emerging literature on program evaluation work and draws upon the authors' experiences conducting evaluations with three community-based organizations funded by the Administration for Community Living to implement programs for individuals with dementia and their family care partners. This article argues for an examination of the expectations of evaluation efforts for translation of research-based trials to practice and emphasizes three main strategies for assessment: (1) development of brief-tailored assessments; (2) measuring fidelity of implementation of the program; and (3) measuring acceptability of the program to clients.